MANAJEMEN MEMBANGUN KELUARGA SAKINAH YANG HIDUP BERBEDA KOTA TEMPAT TINGGAL - Arif Sugitanata (IAIN Palopo, 2020)
Sakinah family management is the science and art of regulating, cultivating and utilizing the elements of life in accordance with the commands and prohibitions of Allah SWT, so that people who are faithful, intelligent and devoted to Allah SWT are realized. A family is considered sakinah when in the life of the family there can be good communication, mutual love, love each other, and are responsible for the benefit of their family members. This research is a literature study, where in compiling this article is from books and literature related to the study discussed, namely the management of building Sakinah families who live in different cities of residence, the material or data presented in this study is qualitative research. , then the method presented uses analytical descriptive. With the results of his research, the Sakinah family is a family that provides calm and tranquility so that the human desires can be achieved physically and spiritually, where management interacts between husband and wife which Long Distnace Marriage can be described into 7 categories namely, instruments used when communicating, initiatives in communication, impressions and messages built on communication, time in communicating, motives in communication, effects after communicating, and authority in communication, apart from intensive communication, in managing or cultivating a family with a Long Distance Marriage condition to become a sakinah family, it should fulfill 6 characteristics of the Sakinah family, namely straightness of intention and strong relationship with Allah, compassion, openness to each other, courteous and wise, communication and deliberation, forgiveness and tolerance, and patience and gratitude.Manajemen keluarga sakinah adalah ilmu dan seni mengatur, mengolah dan memanfaatkan unsur-unsur kehidupan sesuai dengan perintah dan larangan Allah SWT, sehingga terwujudlah insan yang beriman, cerdas dan bertaqwa kepada Allah SWT. Suatu keluarga sudah di anggap sakinah bilamana dalam kehidupan keluarganya dapat terjalin komunikasi yang baik, saling cinta mencintai, saling menyayangi, serta bertanggung jawab atas kemaslahatan anggota keluarganya. Penelitian ini merupakan suatu kajian studi kepustakaan, di mana dalam menyusun artikel ini adalah dari buku-buku dan literatur yang berkaitan dengan kajian yang dibahas yakni manajemen membangun keluarga sakinah yang hidup berbeda kota tempat tinggal, bahan atau data yang disajikan dalam penelitian ini adalah penelitian kualititatif, selanjutnya metode yang disajkan menggunakan deskriptif analitis. Dengan hasil penelitiannya ialah keluarga sakinah adalah keluarga yang memberikan ketenangan dan ketentraman sehingga tercapainya hajat kemanusiaan lahiriah dan batiniah, di mana dalam manejemen berintraksi antara suami dan istri yang Long Distnace Marriage bisa didiskripsikan kedalam 7 katagori yakni, intrumen yang dipakai ketika berkomunikasi, inisiatif dalam komunikasi, kesan dan pesan yang dibangun pada komunikasi, waktu dalam berkomunikasi, motif dalam komunikasi, efek setelah berkomunikasi, dan kewenangan dalam komunikasi, selain komunikasi yang intensif, dalam mengatur atau mengolah sebuah keluarga dengan keadaan Long Distance Marriage agar menjadi keluarga sakinah, maka sudah seharusnya memenuhi 6 karakteristik keluarga sakinah, yakni lurusnya niat dan kuatnya hubungan dengan allah, kasih sayang, saling terbuka, santun dan bijak, komunikasi dan musyawarah, pemaaf dan toleran, dan sabar dan syukur.